BIMBINGAN KONSELING DALAM MERUBAH PERILAKU SISWA DI SEKOLAH - Pratama, Faris Indra (LPPM STKIP PGRI Bandar Lampung, 2019)
This study aims to describe: (1) the implementation of counseling guidance in changing student behavior, (2) the role of teachers and principals in implementing counseling guidance in changing student behavior. This research is a qualitative research. The subjects of this study were the principal, teachers, and students. The data collection techniques used were observation, interview, and documentation techniques. The analysis technique used consists of three components of analysis, namely data reduction, data presentation, and drawing conclusions. This research begins with the preparation stage, research implementation, report preparation and ends with reporting. The result of this research is that the implementation of counseling guidance in TRIMODADI State Elementary School 01 is carried out through the planning, implementation, evaluation, and follow-up stages. Students who have bad behavior are given advice and are guided and directed by an individual approach carried out by the principal and teacher, so that later good behavior can be formed, as well as developing their potential and directed the talents and interests of students. The implementation of this counseling guidance can also solve problems faced by students at school and at home.